The Westphalian System of the Modern International Relations: Violation of Sovereignty, Ignoration of Indigenous Rights, and Extension of Medieval Practices in the Case of Mosul Occupation - Muharrem Doğan (Alternatif Politika)
The Westphalian system refers to the shifting of the supreme political authority from medieval practices to modern sovereign states and related concepts such as sovereignty, non-intervention, and international law. While the system has shaped the Western political environment since 1648, it has in fact not been validated for the rest of the world. In this paper, the idea that the Westphalian system has not opened a new avenue in the discipline of International Relations is exemplified by the case of the British occupation of the Mosul Vilayet. Contrary to the terms of the Mudros Armistice and Woodrow Wilson’s Fourteen Points, the British illegally occupied Mosul. The occupation was a clear violation of the Westphalian principles and thus the British mandate regime encountered resistance from both the Ottoman Empire and further the Republic of Türkiye. Despite all resistance, Mosul was ceded to the Iraqi government under the British mandate after the war.